Factors causing students' anxiety in English speaking classes in Le Quy Don high school, Dong Da, Hanoi - Nguyen, Thi Nhai (University of Languages and International Studies, 2017)
Considered to be an important affective variable, anxiety has been found to be correlated with English-speaking achievement. Andres (2002) asserted that “If we want our students to develop their inherent potential to learn, the affective variables such as (...)